IMPROVING STUDENT LEARNING OUTCOMES BY USING PROBLEM BASED LEARNING MODEL IN LEARNING THEMATIC CLASS III THEME OF GROWTH AND DEVELOPMENT OF LIVING CREATURES - Tantia; Nurmairina (Media Inovasi Pendidikan dan Publikasi, 2024)
This research aims to improve student learning outcomes by using the Problem Based Learning model in class III thematic learning with the theme